Recent Advances in the Roles of HSFs and HSPs in Heat Stress Response in Woody Plants - Tian, Fengxia; Hu, Xiao-Li; Yao, Tao; Yang, Xiaohan; Chen, Jin-Gui; Lu, Meng-Zhu; Zhang, Jin (Frontiers in Plant Science, 2021)
Continuously increasing ambient temperature caused by global warming has been considered a worldwide threat. As sessile organisms, plants have evolved sophisticated heat shock response (HSR) to respond to elevated temperatures and other abiotic stresses, thereby minimizing damage and ensuring the protection of cellular homeostasis. Particularly, for perennial trees, HSR is crucial for their long life cycle and development. HSR is a cell stress response that increases the number of chaperones including heat shock proteins (HSPs) to counter the negative effects on proteins caused by heat and other stresses. There are a large number of HSPs in plants, and their expression is directly regulated by a series of heat shock transcription factors (HSFs). Therefore, understanding the detailed molecular mechanisms of woody plants in response to extreme temperature is critical for exploring how woody species will be affected by climate changes. In this review, we summarize the latest findings of the role of HSFs and HSPs in woody species HSR, and discuss their regulatory networks and crosstalk in HSR. In addition, strategies and programs for future research on the functions of HSFs and HSPs in woody species HSR are also proposed.